2005
DOI: 10.1002/adma.200500759
|View full text |Cite
|
Sign up to set email alerts
|

Control of Carrier Density by a Solution Method in Carbon‐Nanotube Devices

Abstract: A new method for controlling the hole density in single‐walled carbon nanotube field‐effect transistors (SWCNT‐FETs) by solution‐based chemical doping is presented. The use of organic molecules that adsorb onto SWCNTs from solution is investigated. The transfer characteristics of the SWCNT‐FETs exhibit continuous and precise shifts in threshold voltages (see Figure) upon doping with F4TCNQ molecules, even in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 26 publications
2
98
0
Order By: Relevance
“…If tetrafluorotetracyano-p-quinodimethane (F 4 TCNQ, Figure 9 b) is used as a dopant, the threshold voltage is shifted toward a positive gate voltage because of an increase in the doping concentration. [78] Although extensive studies on chemical doping have been performed, the general principle of the underlying mechanism for the choice of the dopant type has not been clarified. Recently, it has been reported that the redox potential difference between CNT and adsorbate is the key parameter in determining the charge-transfer direction.…”
Section: Chemical Dopingmentioning
confidence: 99%
“…If tetrafluorotetracyano-p-quinodimethane (F 4 TCNQ, Figure 9 b) is used as a dopant, the threshold voltage is shifted toward a positive gate voltage because of an increase in the doping concentration. [78] Although extensive studies on chemical doping have been performed, the general principle of the underlying mechanism for the choice of the dopant type has not been clarified. Recently, it has been reported that the redox potential difference between CNT and adsorbate is the key parameter in determining the charge-transfer direction.…”
Section: Chemical Dopingmentioning
confidence: 99%
“…An effective p-type dopant is the strong electron acceptor tetrafluoro-tetracyanoquinodimethane (F4-TCNQ). It has a very high electron affinity (i.e., E ea = 5.24 eV) and has been used successfully as a state of the art p-type dopant in organic light emitting diodes 20,[26][27][28] , carbon nanotubes [29][30][31] and on other materials 32,33 . Recently, the existence of a p-doping effect of F4-TCNQ on graphene has been suggested theoretically 34 and experimentally 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The threshold voltage was shifted toward the positive direction with increasing doping concentration, indicated by an arrow ( figure 3(a)). This is evidence of p-doping in the SWCNT channel, where the Fermi level is downshifted toward the valence band [19]. The Breit-Wigner-Fano (BWF) line at the lower energy side of the G-band in Raman spectroscopy was slightly reduced, once again indicating the charge depletion in the SWCNTs [18,20].…”
Section: Control Of Selective N-or P-type Dopingmentioning
confidence: 88%
“…The intensity of metallic peak near 195 cm −1 in Raman spectroscopy was also significantly reduced, whereas the intensity of the semiconducting peak near 256 cm −1 did not change appreciably. This indicates a selective disintegration of metallic channels [19,28]. The remaining semiconducting channels dominated the conductance of the device.…”
Section: Control Of Doping Concentration and Disintegration Of Metallmentioning
confidence: 93%
See 1 more Smart Citation